Macrophage TRIM21 lactylation exacerbates infection-induced orchitis through enhancing STAT1-mediated CXCL9 and CXCL10 production - Tang, Wenjing; Chen, Wenjie; Li, Na; Li, Wei; Lei, Zhigang; Sun, Wenhui; Xie, Xuan; Jiang, Yihong; Chen, Ying; Xu, Lei; Zhu, Jifeng; Li, Yalin; et al. (Frontiers in Immunology, 2026)
IntroductionInfection-induced orchitis, a leading cause of acquired male infertility affecting 8%–12% of couples globally, is driven by unresolved inflammatory responses following bacterial infection.MethodsWe employed uropathogenic Escherichia coli (UPEC)- and lipopolysaccharide (LPS)-induced orchitis models to define the mechanisms underlying testicular inflammation. We interrogated the cellular sources of CXCL9/CXCL10 and assessed macrophage-driven inflammatory cell recruitment and spermatogenic disruption. Mechanistic studies were focused on lysine lactylation, STAT1 protein stability, ubiquitin–proteasome–mediated degradation, and the role of the E3 ubiquitin ligase TRIM21.ResultsWe demonstrate that macrophages are the predominant source of CXCL9 and CXCL10 responsible for recruiting inflammatory cells into the testis, thereby disrupting spermatogenesis. Mechanistically, the lysine lactylation in macrophages promotes STAT1-mediated CXCL9 and CXCL10 expression by inhibiting ubiquitin–proteasome pathway-mediated STAT1 degradation. Specifically, K345 lactylation of the E3 ubiquitin ligase TRIM21 attenuates ubiquitin–proteasome pathway-mediated STAT1 degradation in macrophages by preventing its interaction with STAT1.DiscussionThis study provides the first evidence that non-histone lactylation (TRIM21 K345) exacerbates inflammatory orchitis and highlights TRIM21 lactylation or CXCL9/10 as promising therapeutic targets for infection-associated male infertility.